An integrative approach to coating/carbide substrate design of CVD and PVD coated cutting tools during the machining of austenitic stainless steel. Issue 4 (March 2020) - He, Q.; Paiva, J.M.; Kohlscheen, J.; Beake, B.D.; Veldhuis, S.C.
Abstract: Machining of hard to cut materials such as austenitic stainless steel presents a challenge due the thermo-mechanical properties of this material, which contribute to intensive buildup edge formation and negatively affect tool life. CVD TiCN + Al2 O3 and PVD AlTiN coatings deposited on cemented carbide substrates are generally recommended for machining austenitic stainless steel. These coatings were deposited by two different methods: (i) PVD AlTiN was deposited on the same substrate material at two different thicknesses (2.5 and 5 μm); (ii) CVD TiCN + Al2 O3 was deposited with the same thickness (5 μm) on two different substrates. A new approach to applying various PVD and CVD (coating + substrate) integrated systems is introduced in this study for austenitic stainless steel machining. The relationship between the coating and substrate characteristics of these material systems and tool performance was assessed. The characteristics of the coating/carbide substrate design were evaluated in terms of chemical, phase composition, architecture, mechanical properties in relation to the tribological and wear performance. The obtained results demonstrate an improvement in tool wear performance and tool life brought about by the surface engineered layer/carbide material with an optimal combination of coating/substrate properties. Based on these findings, a guideline is proposed for further study of the cutting tool life and wear performance of CVD and PVD coated cemented carbide inserts.